2011
DOI: 10.1186/1471-2121-12-14
|View full text |Cite
|
Sign up to set email alerts
|

A STAT3-decoy oligonucleotide induces cell death in a human colorectal carcinoma cell line by blocking nuclear transfer of STAT3 and STAT3-bound NF-κB

Abstract: BackgroundThe transcription factor STAT3 (signal transducer and activator of transcription 3) is frequently activated in tumor cells. Activated STAT3 forms homodimers, or heterodimers with other TFs such as NF-κB, which becomes activated. Cytoplasmic STAT3 dimers are activated by tyrosine phosphorylation; they interact with importins via a nuclear localization signal (NLS) one of which is located within the DNA-binding domain formed by the dimer. In the nucleus, STAT3 regulates target gene expression by bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 68 publications
8
51
0
Order By: Relevance
“…Preclinical studies with the linear formulation of the STAT3 decoy have shown significant antitumor effects in vivo in HNSCC as well as in several other cancers (11,13,23,24). Moreover, a phase 0 clinical trial of the linear STAT3 decoy in HNSCC patients demonstrated pharmacodynamics effects of the decoy on STAT3 target gene expression in tumor tissues (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies with the linear formulation of the STAT3 decoy have shown significant antitumor effects in vivo in HNSCC as well as in several other cancers (11,13,23,24). Moreover, a phase 0 clinical trial of the linear STAT3 decoy in HNSCC patients demonstrated pharmacodynamics effects of the decoy on STAT3 target gene expression in tumor tissues (17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, comparable antitumor effects indicate a lack of dose response at the two dose levels investigated. STAT3 decoy inhibited proliferation and STAT3-mediated gene expression in head and neck squamous cell carcinoma (HNSCC) (10), as well as other cancers (11)(12)(13). Several natural products are also under development to target STAT3, including curcumin, resveratrol and cucurbitacin, among others, although these agents lack specificity (5).…”
Section: Systemic Administration Of a Cyclic Signal Transducer And Acmentioning
confidence: 99%
“…46 The CpG-assisted delivery of STAT3dODN expands the therapeutic potential of decoy strategy, which has been limited to certain types of solid tumors, mainly head and neck cancers. 28,47,48 CpG-STAT3dODN overcomes obstacles in oligonucleotide delivery to hematopoietic cells, which are challenging targets for lipid-and polymer-based approaches. 49 We do not exclude that the antitumor effect of CpGSTAT3dODN is partly derived from concomitant blocking of STAT3 together with STAT1 which reportedly have overlapping tumor-promoting roles in leukemia and certain other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] To verify whether a CpGSTAT3dODN conjugate exerts similar activity, we tested binding of STAT3 to its radiolabeled target DNA sequences using EMSA. As shown in Figure 2A, CpG-STAT3dODN abrogated interleukin-6 (IL-6)-and IL-10-induced STAT3 DNA binding in mouse splenocytes and also reduced constitutive STAT3 activity in KG1a AML cells.…”
Section: Cpg-stat3dodn Inhibits Transcriptional Activity Of Stat3 In mentioning
confidence: 99%
“…Additionally, the modified STAT3 ASO did not inhibit STAT1 or STAT5 underscoring the specificity of the ASO. This is a key finding since another group of STAT3 inhibitors, the STAT3 decoy oligonucleotides, have been shown to inhibit both STAT3 and STAT1 (10,11). STAT1 plays an important role in negatively regulating cell growth (12,13); therefore, cross-inhibition of STAT1 by STAT3 decoys may diminish the antitumor effects of STAT3 blockade.…”
mentioning
confidence: 99%